Symmetry analysis and some new exact solutions of the newell-whitehead-segel and zeldovich equations - Yusuf, Abdullahi; Ghanbari, Behzad; Qureshi, Sania; İnç, Mustafa; Baleanu, Dumitru (Cankaya University, 2019)
The present study offers an overview of Newel-Whitehead-Segel (NWS) and Zeldovich equations (ZEE) equations by Lie symmetry analysis and generalizes rational function methods of exponential function. Some novel complex and real-valued exact solutions for the equations under consideration are presented. Using a new conservation theorem, we construct conservation laws for the ZEE equation. The physical expression for some of the solutions is presented to shed more light on the mechanism of the solutions. © 2019, Cankaya University. All rights reserved.